UPAYA PENCEGAHAN HIPERTENSI PADA LANSIA MELALUI PELATIHAN SENAM HIPERTENSI PADA KADER DI KELURAHAN KOTO BARU NAN XX KOTA PADANG - Arinil Haq; Yeffi Masnarivan; Nurul Aini Humaira; Hanifah Aulia Rafdi; Panesa Anggraila (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Hypertension is the leading cause of premature death worldwide. Physiologically, as someone ages, their risk of developing hypertension increases. The objective of this activity is to enhance the knowledge of health volunteers regarding hypertension and its prevention as an effort to prevent hypertension in the elderly, particularly in the Koto Baru Nan XX Village, Lubuk Begalung District, Padang City. The method involves educational sessions and hypertension exercise training. The activity takes place at the Office of the Head of Koto Baru Nan XX Village, Lubuk Begalung District, Padang City. The target audience comprises 25 health volunteers working in elderly integrated health posts. The program includes lectures on hypertension and a demonstration of hypertension exercises. Additionally, pre-tests and post-tests are conducted to assess participants' knowledge levels before and after the training. The statistical analysis revealed a p-value of 0.0001, indicating a significant difference in the knowledge level before (pre-test) and after (post-test) the hypertension training among the health volunteers in Koto Baru Nan XX Village, Lubuk Begalung District, Padang City. On average, there was a significant increase in the knowledge level of the volunteers after the training. The average knowledge level of the volunteers significantly improved after the educational sessions compared to before. It is hoped that through this activity, health volunteers can encourage and teach hypertension exercises to the attendees of the elderly integrated health posts in Koto Baru Nan XX Village on a regular monthly basis.